Pd(II)/bipyridine catalyzed conjugate addition of arylboronic acids to α, β-unsaturated amides. Issue 25 (22nd June 2016) - Ji, Jiamin; Yang, Zhenyu; Liu, Rui; Ni, Yuxin; Lin, Shaohui; Pan, Qinmin
Graphical abstract: Highlights: Pd-catalyzed conjugate addition of arylboronic acids to α, β-unsaturated amides. The reaction was optimized and the substrates scope investigated. Modest to excellent yields were given for different substrates. The reaction is oxygen and moisture insensitive. Abstract: The Pd(II)/bipyridine-catalyzed conjugate addition of arylboronic acid to α, β-unsaturated amides was developed and optimized, and the reaction was proceeded smoothly in air. A series of arylboronic acid and α, β-unsaturated amide substrates were surveyed, and modest to excellent yields were given.